Organic farming in the context of the bioeconomy - Elena Cofas; Cristina Mihaela Vlad; Rozi Liliana Berevoianu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
The concept of "bioeconomy" or "green economy" is currently highly debated because it is considered to be essential for the future of the world economy. This concept seeks to find both practical solutions applicable in international affairs development environment and long-term alternatives in order to improve the quality of life and eliminate possible impoverishment of the population, due to problems of crisis you no longer are multiple solution. To have a sustainable economic development requires a joint effort between the public and private sectors, in order to separate economic growth from excessive use of resources, the main objective quality of life along with reducing the environmental and social deficit. The transition to bio -based economy implies the practice of investment policies and the connection between economic development, biodiversity, ecosystems, climate change, health and welfare in the medium and long term. These premises must be connected together to achieve sustainable development - considered the resumption of economic growth globally.
Keywords: 330; bioeconomy; environment; agriculture; ecology; sustainable